Answer:
![\boxed{ \bold{ \boxed{ \sf{f( - 4) = 1}}}}](https://tex.z-dn.net/?f=%20%5Cboxed%7B%20%5Cbold%7B%20%5Cboxed%7B%20%5Csf%7Bf%28%20-%204%29%20%3D%201%7D%7D%7D%7D)
Step-by-step explanation:
Given, f ( x ) = - x - 3
Let's find the value of f ( - 4 )
![\sf{f( - 4) = - ( - 4) - 3}](https://tex.z-dn.net/?f=%20%5Csf%7Bf%28%20-%204%29%20%3D%20%20-%20%28%20-%204%29%20-%203%7D)
We know that , ![( - ) \times ( - ) = ( + )](https://tex.z-dn.net/?f=%28%20-%20%29%20%5Ctimes%20%28%20-%20%29%20%3D%20%28%20%2B%20%29)
⇒![\sf{ 4 - 3}](https://tex.z-dn.net/?f=%20%5Csf%7B%204%20-%203%7D)
Subtract 3 from 4
⇒![\sf{1}](https://tex.z-dn.net/?f=%20%5Csf%7B1%7D)
Hope I helped!
Best regards!!
Answer:
<em>x = 3.</em>
Step-by-step explanation:
1. <u><em>Add 2 + 7, and you get 9.</em></u>
2. <u><em>Now find what 3 multiplied by what equals 9.</em></u>
3. <em><u>3 x 3 = 9.</u></em>
4. <em><u>Therefore, x = 3.</u></em>
5. <em><u>3 x 3 - 2 = 7.</u></em>
I wanna say it’s d because of the way it’s set up, i hope this helps if not i’m really really sorry
5x+x-3=9
6x-3=9
cancel out 3 3+3 9+3
6x=12 divide six by 6 and by 12 too.
x=12/6=2
x=2